The Influence of Bureaucratic Ethics and Employee Performance on the Quality of Public Services (Case Study at the DPRD Office in Palopo City) - Nureny Nureny; M. Risal; Muhammad Aqsa (PINISI Discretion Review, 2021)
Lately, the phenomenon of minimal and low service quality has been widely discussed. Of course, this cannot be separated from the pandemic that has occurred for a long time. This condition certainly interferes with the quality of the services provided. This study aims to obtain information and examine the magnitude of the influence of bureaucratic ethics and employee performance on the quality of public services in the Regional House of Representatives office (Indonesia: Dewan Perwakilan Rakyat Daerah / DPRD) in Palopo City. The sample in this study amounted to 87 respondents. Where the sample is selected by the census technique method. The results found that the correlation value of 43.5% means that bureaucratic ethics has a strong enough relationship to service quality, as well as employee performance. The regression coefficient is 17%. Thus it can be interpreted that bureaucratic ethics and employee performance affect service quality by 17%. Bureaucratic ethics and employee performance have a significant and positive effect on the quality of public services with each having a significance value of 0.000 for bureaucratic ethics and 0.035 for employee performance.